2019
DOI: 10.1108/itse-11-2018-0098
|View full text |Cite
|
Sign up to set email alerts
|

Socially orientated digital storytelling among Saudi EFL learners

Abstract: Purpose The current research presents a 14-week experience of developing socially orientated narratives in a digital mode, which involved 60 female Saudi English as a foreign language (EFL) learners. Initially working together, they were later divided into groups of approximately eight members each. The purpose of this research is to determine the benefits and challenges facing EFL leaners who are engaged with socially orientated digital-storytelling tasks. It also explores the nature of creating language-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Due to technological development and advancement in the world, digital tools and appliances have started to become commonplace, especially in the classroom, and this presents an opportunity to expand the abilities of students to learn to speak efficiently using digital storytelling [3,4,18]. Hence, as a result, the objective of the paper is to examine the role of digital storytelling in improving students' speaking abilities.…”
Section: Aim Of Current Systematic Reviewmentioning
confidence: 99%
“…Due to technological development and advancement in the world, digital tools and appliances have started to become commonplace, especially in the classroom, and this presents an opportunity to expand the abilities of students to learn to speak efficiently using digital storytelling [3,4,18]. Hence, as a result, the objective of the paper is to examine the role of digital storytelling in improving students' speaking abilities.…”
Section: Aim Of Current Systematic Reviewmentioning
confidence: 99%
“…When the students' views on the theme of creative thinking were examined, most of them stated that digital story creation activities provided them different perspectives, analytical thinking skills and word fluency, improved imagination and writing, multimedia features made it easier to write stories and enriched the narration, and they could realize the elements of the story more easily thanks to digital story activities. There are many studies in the literature that indicate that creative and critical thinking skills can be developed with digital stories (Abdel-Hack & Helwa, 2014;Ohler, 2008;Czarnecki, 2009;Yüksel et al, 2011;Yang & Wu, 2012;Erişti-Bedir, 2014;Niemi et al, 2014;Hagge, 2017;Akyeampong, 2018;Kim & Lee, 2018;Vinayakumar et al, 2018;Al Khateeb, 2019;Chan, 2019;Moradi & Chen, 2019;Yang et al, 2020). When the opinions about the contribution of digital story creation activities to Turkish lesson were examined, it was observed that the majority of the students stated that digital story creation activities would be beneficial in Turkish lessons.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…DST is a multidimensional learning approach for skills in critical thinking and reading, oral and written communication, and technology [30]. The application of DST in language education can improve language learners' critical thinking, digital literacy, collaboration, their ability to make decisions, and their language learning skills [12,31]. Multiple kinds of literacy, such as digital literacy, visual literacy, technology literacy information literacy, and multicultural literacy, are accommodated and adapted by DST [23].…”
Section: Dst and Enhancement Of Academic Achievementmentioning
confidence: 99%
“…Multimedia tools such as images, soundtracks, and video clips embedded into text or stories directly contribute and lead to the development of written digital stories [12]. Videos play a key role in DST, as they can be striking for both children and adults [13].…”
Section: Introductionmentioning
confidence: 99%